The Effectiveness of the CORE (Connecting, Organizing, Reflecting, Extending) Learning Model on Disaster Mitigation Material to Improve Students’ Learning Outcomes in Geography at Senior High School - Achmad Yusuf; Sholihah, Mar'atus; Rizqina Awaliyah; Afiqoh Billah Izzah (International Journal of Geography, Social, and Multicultural Education, 2026)
This experiment aims to analyze the effectiveness of Connecting, Organizing, Reflecting, Extending (CORE) learning model in improving students learning outcomes on disaster mitigation material in Geography subjects at the Senior High School level. The research employed a quantitative approach with a quasi-experimental design of the Non-equivalent Control Group Design type, involving two classes: an experimental class treated with the CORE model and a control class using conventional learning. The research sample consisted of eleventh-grade students from SMAN 1 Driyorejo, Gresik Regency, selected through purposive sampling and cluster random sampling techniques. Data were collected through pretests and posttests, then analyzed using normality tests, homogeneity tests, and independent sample t-tests. The results showed a significant difference between the learning outcomes of students in the experimental and control classes, with a Sig. (2-tailed) = 0.000 < 0.05, indicating that the CORE model had a significant effect on improving students learning outcomes. The CORE model was considered effective because it actively engaged students through the stages of connecting prior knowledge, organizing concepts, reflecting, and extending understanding within real-life contexts. Therefore, the CORE learning model is deemed feasible to be applied as an innovative alternative to enhance students learning outcomes and conceptual understanding in disaster mitigation material.